The orthogonal measurements approach in estimating spleen size on CT images - Hakan İmamoğlu; Gökmen Zararsız; Mustafa Özdemir; Nuri Erdoğan (Diagnostic and Interventional Radiology, 2020)

(untitled)
PURPOSE:To find out which single measurement and/or linear regression model correlates well with splenic volume using the orthogonal measurements approach.METHODS:The study relied on retrospective analysis of 205 contrast-enhanced abdominal CT examinations carried out in adult patients using a 320-detector CT system. CT volumetry was conducted by a semi-automated, model and threshold based segmentation algorithm that enables voxel-based volume calculation of abdominal organs. The orthogonal measurements were carried out in axial sections by measuring the maximum diameters of spleen projected in sagittal, coronal and transverse planes. In addition, we calculated the diagonal diameter of spleen, which is a derivative of orthogonal measurements. Statistical analysis included calculation of interobserver agreement on orthogonal measurements, followed by model building using linear regression analysis of the measurements.RESULTS:The interobserver agreement between two radiologists was very strong for all orthogonal measurements (r ≥ 0.971). The highest model performance was detected with the diagonal diameter (r2 = 0.956), followed by the superoinferior diameter (r2 = 0.857). Agreement statistics revealed that the regression formula derived from the diagonal diameter outperformed that of superoinferior diameter.CONCLUSION:The diagonal diameter appears to be the best parameter which correlates with splenic volume, whereas the superoinferior diameter can be an alternative in daily CT reporting practice. The orthogonal measurements approach not only provides a high interobserver agreement, but also the diagonal diameter can be translated into ultrasound studies.